MiR-19b-3p and miR-101-3p as potential biomarkers for prostate cancer diagnosis and prognosis - Duca, Rocío Belén (2021)
Prostate cancer (PCa) is the most commonly diagnosed male malignancy worldwide. Early diagnosis and metastases detection are crucial features to diminish patient mortality. High fat diet (HFD) and metabolic syndrome increase PCa risk and aggressiveness. Our goal was to identify miRNAs-based biomarkers for PCa diagnosis and prognosis associated with HFD. Mice chronically fed with a HFD or control diet (CD) were subcutaneously inoculated with androgen insensitive PC3 cells. Xenografts from HFD-fed mice showed increased expression of 7 miRNAs that we named "candidates" compared to CD-fed mice. These miRNAs modulate specific metabolic and cancer related pathways. Using bioinformatic tools and human datasets we found that hsa-miR-19b-3p and miR-101-3p showed more than 1,100 validated targets involved in proteoglycans in cancer and fatty acid biosynthesis. These miRNAs were significantly increased in the bloodstream of PCa patients compared to non-PCa volunteers, and in prostate tumors compared to normal adjacent tissues (NAT). Interestingly, both miRNAs were also increased in tumors of metastatic patients compared to tumors of non-metastatic patients. Further receiver-operating characteristic (ROC) analysis determined that hsa-miR-19b-3p and hsa-miR-101-3p in serum showed poor predictive power to discriminate PCa from non-PCa patients. Hsa-miR-19b-3p showed the best score to discriminate between tumor and NAT, while hsa-miR-101-3p was useful to differentiate between metastatic and non-metastatic PCa patients. Hsa-miR-101-3p was increased in exosomes isolated from blood of PCa patients. Although more detailed functional exploration and validation of the molecular mechanisms are required, we identified hsa-miR-19b-3p and hsa-miR-101-3p with high potential for PCa diagnosis and prognosis.